Who Speaks for Islam? Artificial Intelligence, Fatwa, and Religious Authority in Bangladesh - Jobeda Khanom; Md. Tarequl Islam; Salma Nasrin (Surau Journal of Islamic Studies, 2026)
The rapid advancement of artificial intelligence has begun to exert a profound influence on religious knowledge production and dissemination within Muslim societies, raising urgent questions about authority, authenticity, and accountability. This article examines the implications of artificial intelligence for fatwa issuance and religious authority in Bangladesh, a Muslim-majority country where traditional Islamic scholarship increasingly intersects with digital technologies. As AI-powered systems generate instant responses to religious questions, the boundaries between scholarly interpretation and algorithmic output become blurred, challenging long-established epistemological foundations of Islamic jurisprudence. Drawing on a qualitative and conceptual analysis of scholarly literature published over the past decade, this study explores whether artificial intelligence can legitimately participate in the process of fatwa issuance or whether its role must remain limited to technical assistance. The analysis reveals that while artificial intelligence can enhance access to Islamic knowledge and support scholarly research, it lacks moral agency, contextual sensitivity, and accountability, which are essential for authoritative fatwa issuance. The article argues that unregulated reliance on AI risks fragmenting religious authority and misleading lay Muslims, particularly in digitally saturated environments such as Bangladesh. It concludes that Islamic religious authority must remain rooted in human scholarship, with artificial intelligence functioning strictly as a supplementary tool under institutional and ethical supervision.